An empirical study on the impact of mobile learning apps on college students' physical education learning - Hao Wu; FuGao Jiang (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Introduction: The objective of this study was to assess the mobile learning apps on the college students’ physical education with an emphasis on skill acquisition, theoretical knowledge, motivation, and learning engagement.